PENGARUH MODEL PEMBELAJARAN POSTER COMMENT TERHADAP MOTIVASI BELAJAR PKn SISWA KELAS VIII SMP NEGERI 8 PEKANBARU - Dita Amelia; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the low motivasion of students in classVIII learning at SMPN 8 Pekanbaru. The formulation of the problem in this researchis” whether there is an effect of the application of the Poster Comment learning model on the motivation to learn PKn grade VIII student of SMPN 8 Pekanbar”. This study aims “ to determine the effect of the implementation of the Poster Comment learning model on the learning motivation of PKn students in class VIII of SMPN 8 Pekanbaru”. This research was conducted at SMPN 8 Pekanbaru on July 29 to Agust 23, 2019. This research is a quantitative research that is experimental. The population in this study were eighth grade students of SMPN 8 Pekanbaru. The sample in this study was taken based on a “ random sampling” technique. The sample class is students of class VIII 7 ( experimental class) which is given a Poster Comment learning model, and class VIII 8(control class) is student who are given conventional methods. Data analysis using homogeneity test and “t” test. Based on the results of the study showed that there is an influence of learning motivation between students using Poster Comment learning models and conventional methods at SMPN 8 Pekanbaru ( tcount= 9,25> ttable= 1,66). Where there is an increase in the average score of motivation in the learning of PKn in the experimental class from 21,34 to 22,16 and the average motivation to learn civics from the control class from 19,95 to 20,46. Thus the hypothesis which reads that there is an effect of the use of the Poster Comment learning model on the learning motivation of civics students at SMPN 8 Pekanbaru, can be accepted.Key Words: Poster Comment, Learning Motivation